A new leafhopper genus with description of a new species of Scaphoideini (Hemiptera: Cicadellidae: Deltocephalinae) from Saudi Arabia - El-Sonbati, Saad A.; Wilson, Michael R.; Dhafer, Hathal M. Al (Zootaxa, 2023)
The genus Paranataretus El-Sonbati gen. n. is described from the Kingdom of Saudi Arabia with P. juwayriyae El-Sonbati sp. n. as the type species. Grammacephalus brevis Gnezdilov, 2020 from Madagascar, is placed here in this new genus, as Paranataretus brevis (Gnezdilov) comb. n. A key to the species of Paranataretus is also provided.